1990
DOI: 10.3758/bf03205008
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual buildup of three-dimensional structure from motion

Abstract: We present a set of psychophysical experiments that measure the accuracy of perceived threedimensional (3-D)structure derived from relative motion in the changing two-dimensional image. The experiments are motivated in part by a computational model proposed by Ullman (1984), called the incremental rigidity scheme, in which an accurate 3-D structure is built up incrementally, by considering images of moving objects over an extended time period. Our main conclusions are: First, the human visual system can derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 61 publications
4
48
2
Order By: Relevance
“…This is contrary to the results of Hildreth, Grzywacz, Adelson, and Inada (1990) and Treue et al (1991), which showed that the accuracy of3-D structure recovery from the KDE stimulus improves over time. This apparent contradiction can easily be accounted for in terms of the difference in the time scale.…”
Section: Discussioncontrasting
confidence: 56%
“…This is contrary to the results of Hildreth, Grzywacz, Adelson, and Inada (1990) and Treue et al (1991), which showed that the accuracy of3-D structure recovery from the KDE stimulus improves over time. This apparent contradiction can easily be accounted for in terms of the difference in the time scale.…”
Section: Discussioncontrasting
confidence: 56%
“…One possibility is that the observers were recognizing visible speakers by extracting general facialstructure-from-motion information (e.g., Braunstein, Hoffman, & Pollick, 1990;Christie & Bruce, 1998;Hildreth, Grzywacz, Adelson, & Inada, 1990;Pollick, 1997) and then matching it to the heard voice that best fit that facial structure. Although the results reported above are consistent with this interpretation, a post hoc analysis revealed results less consistent with a structure-from-motion basis.…”
Section: Informational Support For Cross-modal Matchesmentioning
confidence: 99%
“…Any realistic model of the visual system should incorporate a tolerance analysis as a complete description of the stimulus. By way of example we apply the tolerance analysis to the stimuli used in two widely known experiments in which different properties of structure were tested-that is, perceived nonrigidity (Norman & Todd, 1993) and ordering in depth (Hildreth, Grzywacz, Adelson, & Inada, 1990). The analysis explains qualitatively the results of these experiments, illustrating that the results are to a large extent due to stimulus limitations rather than to mechanistic properties of the visual system.…”
mentioning
confidence: 86%
“…This means that the deviations introduced by using orthographic projection are larger than those introduced by stretching along the line of sight. Hildreth et al (1990) provided evidence for the plausibility of the incremental rigidity scheme proposed by Ullman (1984) as a model for the visual system. In this scheme an "internal model" of the 3-D structure of the object is maintained.…”
Section: Perspective Projectionmentioning
confidence: 99%
See 1 more Smart Citation